Preliminary Part - Myanglung Campus, (Intellectual Journal of Academic Research, 2025)
Intellectual Journal of Academic Research is an academic, not for profit, blind peer-reviewed journal of Business, Arts and Social Sciences across disciplines. It aims to provide professors, scholars, Managers, Academicians, Scientists, Industrial professionals, Researchers, students and learned members of the community from all over the world an authentic open-access platform featuring scholarly research, reviews and perspectives on the state of current research on topics of interdisciplinary interest.